MANAJEMEN SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN PADA SDN DAYAH GUCI KABUPATEN PIDIE - Muhammad Nur; Cut Zahri Harun; Sakdiah Ibrahim (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2016)
Abstract: The school management can mean everything pertaining to the management of the educational process to achieve the stated goals, both short-term goals, medium, or panjang.Tujuan term goal of this research was to determine the school management to improve the quality of education, to include: (1) Planning school programs; (2) The implementation of school programs and (3) Barriers faced. This study used a qualitative approach with descriptive methods, techniques of data collection is done through interview, observation guidelines, and documentation. Subjects were principals, supervisors and teachers in primary schools Boarding School Jar Pidie district. Research results found: (1) planning school programs include: teaching programs, including: the need of teachers sharing teaching duties, procurement of textbooks, teaching tools and props, procurement or development of school laboratories, procurement or development of school libraries, system of assessment of learning outcomes, and curricular activities; (2) The implementation of school programs that the strategy adopted to achieve the improvement of the quality of education, include: socialization program, SWOT analysis, problem solving, quality improvement, and monitoring and evaluating the implementation of school programs; and (3) Barriers in planning school programs, among others, lack of community participation and economic difficulties so that their support for the management of low participating schools. It is expected that supervisors in order to direct and supervise principals in improving the quality of education on school program planning, program implementation and obstacles faced by appropriate, effective and efficient so that the quality of education in the schools can be improved.Keywords: Quality Management and the School of EducationAbstrak: Manajemen sekolah dapat diartikan segala sesuatu yang berkenaan dengan pengelolaan proses pendidikan untuk mencapai tujuan yang telah ditetapkan, baik tujuan jangka pendek, menengah, maupun tujuan jangka panjang.Tujuan penelitian ini adalah untuk mengetahui manajemen sekolah dalam meningkatkan mutu pendidikan, dengan meliputi: (1) Perencanaan program sekolah; (2) Pelaksanaan program sekolah dan (3) Hambatan yang dihadapinya. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif, teknik pengumpulan data dilakukan melalui pedoman wawancara, pedoman observasi, dan studi dokumentasi. Subjek penelitian adalah kepala sekolah, pengawas dan guru pada SD Negeri Dayah Guci Kabupaten Pidie. Hasil penelitiannya ditemukan: (1) Perencanaan program sekolah mencakup: program pengajaran, meliputi: kebutuhan tenaga guru pembagian tugas mengajar, pengadaan buku-buku pelajaran, alat-alat pelajaran dan alat peraga, pengadaan atau pengembangan laboratorium sekolah, pengadaan atau pengembangan perpustakaan sekolah, sistem penilaian hasil belajar, dan kegiatan kurikuler; (2) Pelaksanaan program sekolah yaitu strategi yang diterapkan untuk tercapainya peningkatan mutu pendidikan, meliputi: sosialisasi program, analisis SWOT, pemecahan masalah, peningkatan mutu, dan pemantauan dan evaluasi pelaksanaan program sekolah; dan (3) Hambatan dalam perencanaan program sekolah, antara lain kurangnya partisipasi masyarakat dan kesulitan ekonominya sehingga dukungan mereka terhadap manajemen sekolah ikut rendah. Diharapkan kepada pengawas agar dapat mengarahkan dan mengawasi kepala sekolah dalam peningkatan mutu pendidikan tentang perencanaan program sekolah, pelaksanaan program dan hambatan yang dihadapinya secara tepat guna, efektif dan efesien sehingga mutu pendidikan di sekolah tersebut dapat ditingkatkan.Kata Kunci: Manajemen Sekolah dan Mutu Pendidikan